40 A qualitative evaluation of a 1 year pilot study of young people and parents accessing a mental health drop-in centre in a paediatric hospital setting. (30th November 2020) - Fifield, Kate; Xu, Laila; Rojas, Natalia; Catanzano, Matteo; Bennett, Sophie; Sanderson, Charlotte; Coughtrey, Anna; Kerry, Ellie; Liang, Holan; Heyman, Isobel; Shafran, Roz
Abstract : Background: Children and young people with long term physical health conditions (LTC) are known to have higher levels of co-morbid mental health problems than medically healthy children. Evidence-based treatments for mental health problems are effective in children who also have an LTC. A drop-in centre in a paediatric hospital, delivering a range of interventions including onward referral, signposting and guided self-help, may be one way to complement existing mental health services as part of a stepped-care approach. The aim of this study was to understand patients' perspectives of the centre. Methods: 128 patients attending a drop-in centre at Great Ormond Street Hospital were invited to participate. Overall, 35 participated in semi-structured interviews (either in person or by phone) exploring their experience of the drop-in centre. Interviews were audio-recorded, transcribed, and analysed using Framework analysis. Results: Overall, participants found the drop-in centre highly acceptable and reported a positive experience. Reasons for this varied, but broadly focused around four areas:(1) Choice in how to access the intervention and feeling empowered afterwards; (2) Having someone to talk to who could provide them with practical support; (3) Integration and parity of physical and mental health care; (4) The intervention being sufficient to meet their needs and quick to access. Discussion: Participants found the intervention feasible and acceptable. A drop-in centre in a paediatric hospital appears to be a positive and valued adjunct to supplement existing mental health services at GOSH.